Zwischen De- und Reterritorialisierung: Raumproduktion zeitgenössischer US-karibischer Diasporaliteraturen - Brüske, Anne (De Gruyter, 2024)
US-Caribbean diaspora literatures of the 2000s constitute social spaces as spaces of diaspora. This volume looks at the literary production of space in works by Ernesto Quiñónez, Achy Obejas, Edwidge Danticat, and Junot Díaz to identify how these literatures perform the complex task of positioning themselves, their writers, and their ethnic communities between the US and the Caribbean, and between de- and reterritorialization
Keywords: Hochschulschrift; Diaspora; Raum; Obejas, Achy / Days of Awe; Quiñonez, Ernesto / Bodega dreams; Danticat, Edwidge / The dew breaker; Díaz, Junot / The brief wondrous life of Oscar Wao